Model for identifying and eliminating vulnerabilities in software-configurable communication networks based on the apparatus of Markov processes - Коляденко, Ю.Ю.; Лукинов, И.Г. (Radiotekhnika, 2017)
A model for identifying and eliminating vulnerabilities in software-configurable communication networks based on the apparatus of Markov processes is developed. Using this model, knowing the intensity of the flows, it is possible to simulate the processes of receipt of applications for the vulnerabilities detection in real time.